Study on Geometric Programming using Dual Method - Fitriya, Fitriya; Pradjaningsih, Agustina (Majalah Ilmiah Matematika dan Statistika, 2015)
Geometric programming is an optimization technique developed for solving a class of non-linear programming problems. It is used to minimize function which are in the form of posynomial subject to constraints of the same type. To find the solution, this technique consider dual problem that related to primal problem. In this paper, we discuss about minimize solution with constrained of geometric programming problems on the basis of Lagrangian function and Kuhn-Tucker Conditions.